Radical Experiences of Portuguese Social Workers in the Vanguard of the 1974 Revolution. Issue 3 (2nd September 2019) - Silva, Pedro Gabriel
ABSTRACT: This article focuses on the contribution of social workers to the Portuguese democratic transition in the 1970s. Their involvement in urban social mobilizations and in the cooperative movement will offer a perspective on the participation of social workers alongside the Revolutionary process and how they, through engaging with social mobilization, grass-roots initiatives and socio-political activism deployed practices consistent with radical social work frames. It is argued that the Revolution provided the structural conditions for social workers to engage with radical practice and that their intervention constituted a form of agency for socio-political transformation while influencing professional self-representations and professional agency.